2020
DOI: 10.3389/fbioe.2019.00482
|View full text |Cite
|
Sign up to set email alerts
|

First Field Release of a Genetically Engineered, Self-Limiting Agricultural Pest Insect: Evaluating Its Potential for Future Crop Protection

Abstract: Alternative, biologically-based approaches for pest management are sorely needed and one approach is to use genetically engineered insects. Herein we describe a series of integrated field, laboratory and modeling studies with the diamondback moth, Plutella xylostella, a serious global pest of crucifers. A "self-limiting" strain of Plutella xylostella (OX4319L), genetically engineered to allow the production of male-only cohorts of moths for field releases, was developed as a novel approach to protect crucifer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 42 publications
(57 reference statements)
1
29
0
Order By: Relevance
“…Glasshouse trials have shown that repeated releases of these homozygous males can result in eradication of caged wild-type populations and, additionally, delay evolution of Bt resistance (8,9), a finding in agreement with previous modelling (10,11). Wind tunnel experiments have demonstrated that these males retain the ability to locate and respond to female pheromone plumes (12) and open-field trials have shown that these males are able to disperse within a realistic crop setting (13).…”
Section: Introductionsupporting
confidence: 86%
“…Glasshouse trials have shown that repeated releases of these homozygous males can result in eradication of caged wild-type populations and, additionally, delay evolution of Bt resistance (8,9), a finding in agreement with previous modelling (10,11). Wind tunnel experiments have demonstrated that these males retain the ability to locate and respond to female pheromone plumes (12) and open-field trials have shown that these males are able to disperse within a realistic crop setting (13).…”
Section: Introductionsupporting
confidence: 86%
“…There have been numerous field releases of genetically modified insects, although they are only limited to sterile individuals that are not intended to introgress genetic material in the wild population. These include Wolbachia-based programmes for Dengue control in Australia, Asia, and South America [126,127]; sterile males in the malaria vector A. gambiae in Burkina Faso [128,129]; and RIDL systems engineered in the agricultural pests diamondback moth Plutella xylostella in New York [130] and the pink bollworm, Pectinophora gossypiella in Arizona [131], as well as in the Ae. aegypti mosquitoes as a measure against Zika virus outbreaks in the Cayman Island [132,133], Brazil [134], Malasya [135], and Florida [136].…”
Section: Discussionmentioning
confidence: 99%
“…These strains also express the fluorescent protein marker, DsRed, to permit the effective monitoring of the presence of such strains in the field. Recently, a series of open release trials took place in Geneva (NY, USA) with adult male fsRIDL GM diamondback moths (strain OX4319L) and wild-type counterparts to test dispersal, persistence and field survival of the local diamondback moth population in a cabbage field (Shelton et al, 2020). Further open release trials are recommended by Shelton et al (2020) to assess suppression efficacy.…”
Section: Release Of Genetically Modified Insects With a Dominant (Femmentioning
confidence: 99%
“…Recently, a series of open release trials took place in Geneva (NY, USA) with adult male fsRIDL GM diamondback moths (strain OX4319L) and wild-type counterparts to test dispersal, persistence and field survival of the local diamondback moth population in a cabbage field (Shelton et al, 2020). Further open release trials are recommended by Shelton et al (2020) to assess suppression efficacy. Previous glasshouse experiments demonstrated the effectiveness of this approach (Harvey-Samuel et al, 2015).…”
Section: Release Of Genetically Modified Insects With a Dominant (Femmentioning
confidence: 99%